PENERAPAN METODE RETELLING STORY BERBANTUAN MEDIA BONEKA TANGAN UNTUK MENINGKATKAN KETERAMPILAN BERBICARA (BERCERITA) SISWA KELAS IV SD NEGERI 9 TAMBAKASRI - Yunita Dewi, Lidiana; Dwi Agus Setiawan; Denna Delawanti Chrisyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Elementary education plays an essential role in developing students’ language skills, particularly speaking ability. One of the speaking skills that should be emphasized at the elementary school level is storytelling. Based on preliminary observations conducted in Grade IV of SD Negeri 9 Tambakasri, approximately 50% of students had not achieved the Minimum Mastery Criteria (KKM) of 75 in storytelling skills. Students demonstrated low self-confidence, difficulty in organizing story sequences coherently, and inaccuracies in pronunciation, intonation, and expression. These problems were caused by the use of traditional teaching methods and the limited application of engaging learning media. This study aimed to improve the storytelling skills of fourth-grade students at SD Negeri 9 Tambakasri through the implementation of the retelling story method assisted by hand puppet media. The research employed a Classroom Action Research (CAR) design conducted in several cycles, consisting of planning, implementation, observation, and reflection. The retelling story method allowed students to retell stories using their own words, while hand puppet media functioned as visual learning aids to enhance students’ interest, confidence, and understanding of story structure. The results of this study are expected to indicate improvements in students’ storytelling skills in terms of fluency, accuracy of pronunciation and intonation, vocabulary usage, expression, and self-confidence. Therefore, the retelling story method assisted by hand puppet media can be an effective and enjoyable alternative for improving storytelling skills in elementary school students.